Challenges and Risks Faced Mobile Banking Services and Ways to Confront and Limit Them - Sultan, Khaldoon; Abed Nour, Safaa (Journal of Legal Sciences, 2023)
This study deals with the challenges and risks faced by mobile banking services and their plagiarism and reduction, the issue of risk management and review, as it acquires financial importance for banks that provide electronic mobile banking services, as included by the Basel Committee, financial accounting via mobile phone, and in line with treason works Traditional commercial banks invest in modern ones, including mobile phones.